Parkinson's Disease Understanding Pathophysiology and Developing Therapeutic Strategies - Chandra Yenisetti, Sarat (IntechOpen, 2018)
Parkinson's disease (PD) is the second most common neurodegenerative disorder results due to loss of dopamine producing brain cells. Knowledge relating to PD condition has been known since 5000BC, however no effective therapeutic strategies are available till today. Therefore it is important for neurobiologists to work further by taking advantage of modern scientific methods and develop appropriate therapeutic strategies. Efforts in this direction are worthy as they will reduce the burden of PD among elderly, who are already burdened with age related systemic degenerative processes. This book is a humble effort in that progressive direction. It has chapters covering multiple aspects relating to etiology, pathophysiology of PD, available and futuristic therapeutics strategies. Therefore it will be of interest to common man, biomedical researchers and clinicians. This is one small step in a direction "to reduce the burden of neurological disease."